Cognitive robotics - Samani, Hooman (CRC Press/Taylor & Francis Group, 2016)
"This edited collection presents theoretical research in cognitive robotics. It takes a multidisciplinary approach that considers the artificial intelligence, physical, chemical, philosophical, social, cultural, and ethical aspects of this rapidly emerging field. The editor is a prominent researcher whose lovotics research into emotional bonds with robots is widely recognized. Supplying an accessible introduction to cognitive robotics, the book considers computational intelligence for cognitive robotics based on informationally structured space. It examines how people respond to robots and what makes robots psychologically appealing to humans. The book contextualizes concepts in the history of studies on intelligence theories and includes case studies of different types of robots in action. Although ideal for robotics researchers and professionals, this book is also suitable for use as a supporting textbook in advanced robotics courses at both the undergraduate and graduate levels"- Resumé vydavatel
Keywords: robotika; roboty; roboty -- sociální aspekty; řídicí systémy; robotics; robots; robots -- social aspects; control systems; sborníky; elektronické knihy; papers of several authors; electronic books